High-voltage pulsed radiofrequency to treat secondary glossopharyngeal neuralgia - Radiofrequenza pulsata ad alto voltaggio per trattare una nevralgia glossofaringea secondaria - Carmelo Costa; Francesco Inserra; Filippo Indelicato (Publiediting, 2020)
Glossopharyngeal neuralgia (GN) is a quite uncommon neuropathic face pain syndrome. In the classic form pain occurs as recurring paroxysmal, unilateral, short time lasting and shooting or electric shock-like attacks in the sensory area of the ninth cranial nerve. The secondary form can be caused by surgery injuries, cancer, infections, vascular malformations or elongated styloid process (Eagle syndrome). We present the case of a patient with GN occurred eight months after stereotactic radiosurgery of acoustic neuroma. Pain was drug-resistant but responded significantly to high voltage pulsed radiofrequency CT-guided treatment. No complications were reported neither throughout the procedure nor in the immediate postoperative period.